2017
DOI: 10.1016/j.isprsjprs.2017.07.006
|View full text |Cite
|
Sign up to set email alerts
|

Spectral analysis of amazon canopy phenology during the dry season using a tower hyperspectral camera and modis observations

Abstract: The association between spectral reflectance and canopy processes remains challenging for quantifying large-scale canopy phenological cycles in tropical forests. In this study, we used a tower-mounted hyper-spectral camera in an eastern Amazon forest to assess how canopy spectral signals of three species are linked with phenological processes in the 2012 dry season. We explored different approaches to disentangle the spectral components of canopy phenology processes and analyze their variations over time using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 61 publications
2
36
0
1
Order By: Relevance
“…Seasonality effects on plant phenology can reduce our ability to extract biophysical information from remote sensing observations in the Amazon, e.g., [47]. Without tree-by-tree phenology field data to support a proper analysis, we are unable to determine the exact impact of seasonality on our detection, but we expect that it may have a minor to moderate impact.…”
Section: Discussionmentioning
confidence: 99%
“…Seasonality effects on plant phenology can reduce our ability to extract biophysical information from remote sensing observations in the Amazon, e.g., [47]. Without tree-by-tree phenology field data to support a proper analysis, we are unable to determine the exact impact of seasonality on our detection, but we expect that it may have a minor to moderate impact.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, two recent studies also have shown that leaf spectroscopy provides an accurate, rapid means to assess leaf age at both individual and community scales Wu et al, 2017). Furthermore, some studies also suggest that it is possible that spectroscopy-based models of leaf V c,max25 and age could be extended to the canopy scale by leveraging imaging spectroscopy instrumentation on tower, unmanned aerial systems and manned airborne platforms De Moura et al, 2017). These developments highlight the potential to map changes in V c,max25 and leaf age over unprecedented spatial and temporal scales.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, remote sensing data offer a viable means to explore spatial and temporal information, providing a range of insights about the tropical ecosystems (Chambers et al, 2007;Yang et al, 2013). The spectral indices and time series approaches have been widely used across the Amazon basin detecting seasonal changes of rainforest vegetation (Hilker et al, 2015;Moura et al, 2017), urban mapping (Lu et al, 2011), sediment dynamic in the rivers (Park and Latrubesse, 2014;Lobo et al, 2016), cropland and pasture monitoring (Arvor et al, 2012;Arantes et al, 2016;Aguiar et al, 2017). While optical sensors allow the synoptic view of the landscape dynamics (Barbosa et al, 2015), the top-of-atmosphere (TOA) radiance measured by satellite sensors is not only dependent on the ground properties, but is often distorted by atmospheric constituents (Okin and Gu, 2015;Vermote and Kotchenova, 2008).…”
Section: Introductionmentioning
confidence: 99%